The short-term economic effects of COVID-19 and risk-coping strategies of low-income households in Kenya: A rapid analysis using weekly financial household data - Wendy Janssens; Menno Pradhan; Richard de Groot; Estelle Sidze; Hermann Donfouet; Amanuel Abajobir (Tinbergen Institute, 2020)
This research assesses how low-income households in Western Kenya coped with the immediate economic consequences of the COVID-19 outbreak. It uses granular financial data from weekly household interviews covering six weeks before the first case was detected in Kenya to five weeks after. Our results suggest that income from work decreased with almost one third and income from gifts and remittances reduced by more than one third since the start of the pandemic. Nevertheless, household expenditures on food remained at pre-outbreak levels after preventive measures were implemented. We do not find evidence that households coped with reduced income through increased borrowing, selling assets or withdrawing savings. Instead, they gave out less gifts and remittances themselves, lent less money to others and postponed loan repayments. Moreover, they significantly reduced expenditures on schooling and transportation, related to the school closures and travel restrictions. Taken together and despite their affected livelihoods, households managed to keep food consumption at par, but this came at the cost of reduced informal risk-sharing and social support between households.
Keywords: I38; O12; I15; 330; COVID-19; lockdown; economic effects; food security; risk-coping; East-Africa; Kenya